Cryopreservation of zygotic and somatic embryos of oil palm (Elaeis guineensis jacq.) for germplasm conservation - Periasamy, Suranthran (2012)
The objective of this research is to establish of refinement protocol on cryopreservation of zygotic embryos (ZE) (direct desiccation) and somatic embryos (SE) (vitification techniques) of oil palm (Elaeis guineensis Jacq.). To support the growth and development of oil palm ZE, initially, the effect of plant growth regulators (PGR) and activated charcoal (AC) on in vitro regeneration and seedlings development from oil palm (varieties Dura and Tenera) ZE was assessed. ZE were cultured on Murashige and Skoog (MS) medium supplemented with a blend of 0.05 or 0.1 mgL-1 of each PGR (gibberellic acid, 6-benzlaminopurine and α-naphthaleneacetic acid) with or without 2 gL-1 AC. Growth and development of the embryos were affected by the type of medium. ZEs cultured on MS medium supplemented with both PGR and AC enhanced shoot initiation and subsequent plantlet development, while PGR supplemented MS media without AC led to abnormal growth suggesting that AC is indispensable for oil palm in vitro seedlings regeneration. The best medium for growth and development of plantlets was MS medium supplemented with 0.1 mgL-1 PGR and 2 gL-1 AC which showed significant variation compared to the remaining media formulations. After that, the effects of desiccation and freezing on survival of oil palm ZE, were assessed using the above mentioned media. ZE of variety Dura and hybrid Tenera were subjected to desiccation for 8 h. ZE were analysed for free water content (WC) and resurgence ability after each desiccation and freezing period. The survival was at its maximum (Dura 80%) and (Tenera 70%) when the desiccated ZE containing ~0.14 gH2O g-1 fw of WC and below in which abnormal or no survival was recorded. This optimal WC not only assisted oil palm ZE to sustain their cellular integrity but also retained their regeneration potential following cryopreservation. On the contrary, ZE with WC above 0.24 gH2O g-1 dw or below 0.16 gH2O g-1 dw lost their viability as well as their cellular integrity attributable to either excess WC or excessive loss of free water, after desiccation and successive freezing. Scanning electron microscopic observations confirmed that there was no noteworthy distinction in morphology of epidermal layer after desiccation and successive freezing. Thus for successful cryopreservation of oil palm ZE, they should be desiccated to a WC of 0.14 gH2O g-1 fw and 80% survival can be obtained. In the experiment concerning cryopreservation of oil palm clonal material using polyembryoid, the effect of various loading solutions (LS) and vitrification solutions (VS) and their time of exposure on survival of polyembryoid in liquid nitrogen (LN) was evaluated. In vitro grown polyembryoid of oil palm were successfully cryopreserved by vitrification with 45% survival. Individual polyembryoid, which were separated and excised from two-month old (from polyembryoid initiation) culture clumps, were precultured in liquid MS medium supplemented with 0.5 M sucrose for 12 h and then treated with a mixture of 10% (w/v) DMSO plus 0.7 M sucrose for 30 min all at 26 ± 2°C. Osmo-protected polyembryoid were first treated with VS (PVS2 - 30% (w/v) glycerol plus 15% (w/v) EG plus 15% (w/v) DMSO plus 0.4 M sucrose) for 5 min at 26 ± 2°C and plunged directly into LN. Following rapid warming in a water-bath at 38 ± 2°C for 90 sec, the polyembryoid were washed for 20 min at 26 ± 2°C with liquid MS medium containing 1.2 M sucrose. They were then transferred onto solid MS medium 3% (w/v) sucrose and 0.75% (w/v) agar. The polyembryoid were kept in the dark for seven days prior to exposure to light (16 h photoperiod cycle). Direct shoot initiation was observed approximately after three weeks after culture. In overall, best culture medium for ZE growth is MS with 0.1 mgL-1 PGR and 2 gL-1 AC and approximately 0.14 gH2O g-1 fw of WC shows highest survival in LN treatment for both Dura and Tenera; 12 h 0.5 M sucrose precultured polyembryoid treated with L5, 30 min and PVS2, 5 min was successfully cryopreserved in this study.